Vegetation and Its Impact According to User’s Perception: Case of North Land Use Plan of Guelma City - Bechaa Teqwa; Dahmani Krimo; Alkama Djamel (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The vegetation takes a primordial place in the reflection on our urbanity for the balance of the ecosystem. Guelma, attractive Mediterranean city, by the picturesque character of its site, incites to discover it from the inside to better understand its urban landscape. In this same regard our study focuses on the north land use plan of the city. Today, the city is characterized by accelerated urbanization, which leads to the consumption of natural resources. One of the consequences of these phenomena is the deterioration of green substrates, by fragmentation of natural environments and agricultural areas. The objective is to show the role of vegetation in the satisfaction of the users of north land use plan of Guelma city, this can only be done through a survey of the various users of this city. Finally, recommendations dedicated to the proposal of the implementation of ecological planning to the management.